2015
DOI: 10.1186/s13028-015-0164-5
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein: quantitative marker of surgical trauma and post-surgical complications in dogs: a systematic review

Abstract: C-reactive protein (CRP) is a major acute phase protein showing increasing serum concentrations in dogs with systemic inflammation following e.g., surgery, trauma, infections, or neoplasia. CRP is a useful diagnostic marker of systemic inflammation in dogs and automated assays have been validated for reliable measurements for routine diagnostic purposes. In the present study available evidence for the use of CRP as a marker of surgery related systemic inflammation in dogs was reviewed and assessed. Two main th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 52 publications
4
42
0
Order By: Relevance
“…24,27 Numerous authors have advocated the inclusion of CrP in standard inflammatory panels in dogs, as it reacts quicker and more profoundly than leucocytes. 25,27,28 As seen in previous studies investigating pyometra or sepsis, 26,27,29,30 we were able to detect that CrP more reliably documented the failure to control local infection and subsequent non-successful wound closure compared with leucocytes. We also found that it is not only the absolute value at the beginning of therapy, but rather the development over time that made the difference.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…24,27 Numerous authors have advocated the inclusion of CrP in standard inflammatory panels in dogs, as it reacts quicker and more profoundly than leucocytes. 25,27,28 As seen in previous studies investigating pyometra or sepsis, 26,27,29,30 we were able to detect that CrP more reliably documented the failure to control local infection and subsequent non-successful wound closure compared with leucocytes. We also found that it is not only the absolute value at the beginning of therapy, but rather the development over time that made the difference.…”
Section: Discussionsupporting
confidence: 74%
“…23 C-reactive protein is one of the major acute phase proteins in dogs. [24][25][26] It is a pattern recognition molecule that binds to pathogens (bacterial-membrane) and cells undergoing death. 23 It is mainly generated by the liver where the production of positive acute phase proteins is increased, while albumin synthesis is decreased by inteleukin-6 and interleukin 1β.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for withdrawal were not noted for each case. A review evaluating CRP as a marker of inflammation after surgical procedures showed that the risk for bias in studies about CRP in dogs is elevated due to its lack of specificity (28). We have encountered similar bias in our study, making it difficult to draw conclusions from a field study.…”
Section: Discussionmentioning
confidence: 73%
“…C-reactive protein (CRP) is one of acute phase proteins and being a marker for several diseases (Christensen et al, 2015;Hillström et al, 2016;Bremer et al, 2017;Severo et al, 2018). When the inflammatory cells are activated by different inflammatory stimuli, the acute phase response is triggered and different cytokines are released from the inflammatory cell (Hillström et al, 2015;Gommeren et al, 2018).…”
Section: Research Articlementioning
confidence: 99%